Study protocol for an open-label, single-arm, multicentre phase II trial to evaluate the efficacy and safety of combined triplet therapy and olanzapine for prevention of carboplatin-induced nausea and vomiting in gynaecological cancer patients - Iihara, Hirotoshi (BMJ Open, 2019)
INTRODUCTION: Carboplatin (CBDCA) administered at a dosage of 4 mg/mL/min or more area under the blood concentration-time curve (AUC) is considered to be ranked as the highest chemotherapy-induced nausea and vomiting (CINV) risk of the moderately emetogenic chemotherapy agents. The complete response (CR) rate for preventing overall CINV, defined as no emetic episodes and no use of rescue medication, for standard triplet antiemetic therapy (5-HT(3)RA, 5-hydroxytryptamine-3 receptor antagonist; NK(1)RA, neurokinin-1 receptor antagonist; DEX, dexamethasone) was approximately 60% in gynaecological cancer patients receiving CBDCA-based therapy. Further improvement in antiemetic treatment is needed to optimise care. This trial is to evaluate the efficacy and safety of using 5 mg olanzapine (OLZ) plus standard triplet antiemetic therapy for CINV after AUC ≥4 mg/mL/min CBDCA combination therapy in gynaecological cancer patients. METHODS AND ANALYSIS: This trial is an open-label, single-arm, multicentre phase II trial. Patients who receive CBDCA (AUC ≥4)-based therapy and have never been administered moderate to high emetogenic chemotherapy will be enrolled. All patients will receive OLZ (5 mg oral administration on days 1–4, after supper) in combination with 5-HT(3)RA, NK(1)RA and DEX. The primary endpoint is the CR rate during the overall period (0–120 hours). Testing the hypothesis that this regimen can improve CR rate from 60% (null hypothesis) to 75% (alternative hypothesis) with a one-sided type I error of 0.1 and power of 0.8 will require 53 patients. Considering the dropout rate, the target sample size is set at 60. ETHICS AND DISSEMINATION: The study protocol was approved by the institutional review board at each of the participating centres. Data will be presented at international conferences and published in peer-reviewed journals. TRIAL REGISTRATION NUMBER: UMIN000031646.